International Biotechnology Conference on Estate Crops 2017 (IOP conference series. Earth and environmental science, 2018)
Preface Biotechnology techniques are carrying forward plantation crop development in attempts to understand the genetic basis of the crops, to produce tissue-cultured plantlets on a large scale, to employ molecular breeding of new cultivars for increased yield, resistance to pests and tolerance to environmental stresses, and to use microorganisms for bio-based products, soil healthiness and waste treatment. The Indonesian Research Institute for Biotechnology and Bioindustry (IRIBB) has organized an International Biotechnology Conference on Estate Crops 2017 on 18- 20 October 2017 in Grand Sahid Jaya Hotel Jakarta, Indonesia. This Conference was in conjunction with the World Plantation Conferences and Exhibition 2017 (WPLACE-2017) on 18 October 2017. WPLACE-2017 provided General Topics (GTs) on related subjects. It is truly meaningful for the Indonesian Research Institute for Biotechnology and Bioindustry (IRIBB) to hold the first International Biotechnology Conference on Estate Crops 2017 (IBCEC-2017), an international forum for biotechnology and exposition. The institution was founded in 1901 by the Dutch colonial government under the name of Centrale Proefstations Vereniging (CPV). In 1957, during the expropriation firms of the Dutch plantations in Indonesia, CPV was repossessed by the Indonesian government. For many years since the CPV, it has undergone many name changes until 2015 in which the Indonesian Research Institute for Biotechnology and Bioindustry (IRIBB) was officialised. The IRIBB carries a vision to be an innovative and internationally research-based institution in biotechnology and bioindustry. The conference program included honourable lectures from eminent experts on the success stories and the recent development of biotechnology such as bioinformatics, genome editing, genomic selection, in vitro propagation, phytobiome, biostimulant, bioplastic, biopesticide, and biofermentation.